2011
DOI: 10.5539/gjhs.v3n2p50
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Modern Contraceptive Practices among Selected Married Women in a Public University in Malaysia

Abstract: In Malaysia, only 30% of the married women use modern contraceptive methods. Low usage of contraceptive methods, results in high rates of unwanted pregnancies and its consequence which includes; psychological problems physical health and unsafe abortion. The main purpose of this study is to understand the barriers of modern contraceptive practices among women in University Putra Malaysia. This study was carried out through two main research questions: 1.What is the women's perceptions of modern contraceptive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…In the present study, those women who had at least primary education had good attitude to modern contraceptive use than those women who could not read and write. Studies elsewhere revealed a similar pattern of relationship between educational status and maternal health service including family planning utilization [30] [31].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In the present study, those women who had at least primary education had good attitude to modern contraceptive use than those women who could not read and write. Studies elsewhere revealed a similar pattern of relationship between educational status and maternal health service including family planning utilization [30] [31].…”
Section: Discussionmentioning
confidence: 58%
“…In Muslim dominated countries such as Pakistan [28], Egypt [29] and Malaysia [30] the justification not to use family planning is religious. In the present study, region was not a statistically significant factor.…”
Section: Discussionmentioning
confidence: 99%
“…Neoclassical theory suggests that an investment in human capital increases and as more women participate in the labour market, the fertility behaviour of households is bound to change, in favour of fewer children [32]. From the finding, 56.4% of respondents had ever used the calendar method as a natural family planning method [9]. It is, however, inconsistent with findings where women did not know of the calendar method as a natural family planning method [4].…”
Section: Discussionmentioning
confidence: 99%
“…Again, it plays an important role in decreasing maternal mortality [8]. The realization of the important role of family planning methods and the speed with which this knowledge was put to practice worldwide is perhaps the most remarkable achievements [9]. This notwithstanding, people in lower income economies are still battling with the rapid and uncontrolled increase in population [10].…”
Section: Introductionmentioning
confidence: 99%
“…For many women and couples around the world, religious, cultural, gender, and social norms prevent the use of family planning (Anonymous, 2011). The researchers were particularly interested to identify the socio cultural barriers to use the modern family planning practices.In Pakistan, several obstacles identified to the use of modern contraceptives including; husbands' opposition, fear of side effects, health concerns, and dissatisfaction with sexual sensation when using them (Najafi, 2011). In particular, women were ten times more likely to have used a family planning service if her husband approved (Stephenson, 2004).…”
Section: Introductionmentioning
confidence: 99%